Sliding block analysis of lateral spreading based on centrifuge results. Issue 2 (June 2002) - Sharp, Michael K.; Dobry, Ricardo
Abstract : A number of lateral spreading centrifuge tests conducted at RPI at 50 g on fine Nevada sand are reviewed and used to produce a first order analytical model based on wave propagation theory which predicts well the measured patterns of permanent ground displacement. In-flight base shaking of a slightly inclined laminar box containing a homogeneous saturated sand deposit induces liquefaction and lateral spreading. Both water and a viscous fluid fifty times more viscous than water are used as pore fluid in the tests. The observed lateral displacement profiles during and at the end of shaking are very different: smooth and more or less parallel profiles in the "viscous fluid" tests, and profiles containing a concentrated straining zone in the "water" tests. Other differences include stabilization of the depth of liquefaction at an intermediate depth early in the shaking in the "water" tests, compared with downward propagation of the liquefaction front throughout the shaking accompanied by a closely related downward propagation of a deformation front in the "viscous fluid" tests. A close correspondence was observed in all tests between the liquefaction/nonliquefaction boundary and the zone of high soil straining controlling the lateral spreading phenomenon. These observations are used to produce the first order analytical model, which predicts that all permanent displacements are generated within a transition zone centered around the liquefaction front and bounded below by the deformation front. The analytical model predicts successfully the measured displacement patterns in both "viscous fluid" and "water" tests, by allowing the transition zone to propagate downward or remain stationary during the shaking, respectively. Approximating the transition zone by a sliding plane reduces the model to the popular rigid sliding block analysis with either a stationary or moving sliding plane.